(untitled) (Indian Journal of Chemistry (IJC), 2024)
In light of the current scarcity of effective antimicrobial and antimycobacterial drugs, often limited by factors such as narrow spectrum, lack of oral formulations, and suboptimal pharmacokinetics, we embarked on synthesizing a series of hybrid pyridine-thiophene clubbed pyrazoline molecules (designated as 8a-j) to enhance their potency. This was achieved through a one-pot multicomponent reaction involving substituted benzylideneacetophenone (7a-j) and hydrazine hydrate catalyzed by CH3COOH in ethanol at reflux temperature. Structure of all the compounds (8a-j) were confirmed by employing elemental analysis, ESI-mass, 1H NMR and FTIR which supported the suggested structures. Newly synthesized compounds were screened for antibacterial, antifungal and antimycobacterial activities. Compounds 8a, 8d, 8f, 8g, 8h, and 8j were identified as promising candidates for investigating in vitro antimicrobial and antimycobacterial activities in comparison to standard antibiotics. Additionally, studies on molecular docking targeting the functioning site of the KS-AT domains of Mycobacterial Pks13 enzyme revealed binding affinities ranging from -10.5 to -9.8 kcal/mol. The docking score for the most active compound, 8i was found to be -10.5 kcal/mol in PYRX Autodock VINA, demonstrating its favorable accommodation within the active site of the PKs enzyme.